Sustainable biological systems for agriculture : emerging issues in nanotechnology, biofertilizers, wastewater, and farm machines - Goyal, Megh R. (Megh Raj); Apple Academic Press (Toronto ; New Jersey : Apple Academic Press, 2018)
Sustainable Biological Systems for Agriculture: Emerging Issues in Nanotechnology, Biofertilizers, Wastewater, and Farm Machines explores and introduces the use of nanotechnology, biofertilizers, and design of farm machines in agriculture. The contributions are from India, Africa and the USA; the chapters emphasize sustainable solutions for the enhancement of agriculture processes. The volume provides a wealth of information on new and emerging issues in this interdisciplinary field.
part PART I: Potential Applications of Nanotechnology in Biological Systems -- chapter 1 Applications of Nanotechnology in Agriculture$1 (BA Review: Concepts, Aspects, Prospects, and Constraints /s Saurabhh Jain -- chapter 2 Nanotechnology Applications in Agricultural and Biological Engineering / Deepika Choudhary -- chapter 3 Potential of Nanotechnology in Dairy Processing: A Review / Lohith Kumar -- part PART II: Emerging Issues, Challenges and Specific Examples of Nanotechnology for Sustainable Biological Systems -- chapter 4 Plant-Nanoparticles (NP) Interactions$1 (BA Review: Insights into Developmental, Physiological, and Molecular Aspects of Np Phytotoxicity /s Shweta Jha -- chapter 5 Extracellular and Intracellular Synthesis of Silver Nanoparticles / Prasanna Subramanian -- chapter 6 Biosensors: A Potential Tool for Detection of Microbial Contaminants for Food Safety / Anurag Jyoti -- chapter 7 Modeling and Fermentatation Aspects of Pullulan Production from Jaggery / G. V. S. Rama Krishna -- chapter 8 Antibiotic Resistance of Staphylococcus Aureus: A Review / Divya Lakshminarayanan -- part PART III: Potential of Nano- and Bio-fertilizers in Sustainable Agriculture -- chapter 9 Role of Nanofertilizers in Sustainable Agriculture / Arti Goel -- chapter 10 Role of Seaweed and Water Hyacinth Biofertilizers: Quality and Production of Okra / Savan D. Fasara -- chapter 11 Role of Seaweed and Water Hyacinth Biofertilizers: Quality and Production of Cowpea (Vigna Unguiculata) / Bhumika P. Chadamiya -- part PART IV: Emerging Focus Areas in Biological Systems -- chapter 12 Fishpond Wastewater: The Potential Irrigation Source -- chapter 13 Urban Wastewater Treatment Systems: Assessment of Removal Efficiency Based on Microbial Pathogens: A Case Study in Mysore, India / Jessen George -- chapter 14 Phytochemical Screening, Formulation and Evaluation of Polyherbal Ointment Containing Mimosa Pudica and Samadera Indica / P. H. Rajasree -- chapter 15 Bioinformatic Advancements in Post Translational Modifications (PTMs): An Experimental Approach / Saurabhh Jain -- chapter 16 Approximating the Quadratic Programming (QP) Problem / Elias Munapo -- part PART V: Performance of Farm Machines for Sustainable Agriculture -- chapter 17 Citrus Fruit Harvester / Mrudulata Deshmukh -- chapter 18 Rotary Harvesting Mechanism: Sorghum / Mrudulata Deshmukh -- chapter 19 Performance of Stationary Power Cutter: Sugarcane Sets and Sorghum / S. K. Thakare -- chapter 20 Tractor Three-Point Linkage System: Computer-Aided Design and Simulation Analysis / Thaneswer Patel.
Keywords: SCIENCE / Life Sciences / Botany; Agricultural engineering; Agricultural machinery; Biofertilizers; Nanotechnology; TECHNOLOGY & ENGINEERING / Agriculture / General